Gut microbiota and stress ulcers: unraveling the neurotransmitter connection - Abdel-Sater, Khaled A.; Hassan, Heba A. (Frontiers in Neuroscience, 2025)
BackgroundNeurotransmitters are key signaling molecules in the brain-gut axis, may be involved in stress-induced ulcer damage.ObjectiveThis study aims to address the relationship between gut microbiota and the stress response is examined in this review, with a focus on how neurotransmitters moderate the impact of stress on mucosal integrity and gut health. Understanding these mechanisms may open new avenues for therapeutic interventions targeting the brain-gut axis.MethodsA literature search was completed using PubMed, Web of Science, Cochrane, PsycINFO, Scopus and Embase databases for clinical and preclinical studies related to stress ulcer, gut microbiota and gut brain axis that published in English until November 2024.ResultsThe gut microbiota plays important role in preserving the health of the digestive system and influencing the body’s stress response through various pathways, including the enteric and autonomic nervous systems. This results in the production of microbial metabolites such as bile acids, tryptophan, and short-chain fatty acids that enter the bloodstream and go to the brain. Microbial neurotransmitters change the brain’s gastrointestinal axis.ConclusionThe connection between stress ulcer, neurotransmitters, and the gut microbiota was outlined in this review.